2013
DOI: 10.1080/17457300.2013.863784
|View full text |Cite
|
Sign up to set email alerts
|

Injuries from falling objects in the United Arab Emirates

Abstract: Our aim was to study the demography, anatomical regions injured, severity, and outcome of hospitalised trauma patients who were injured by falling objects in order to give recommendations regarding their prevention in the UAE. All trauma patients who were injured by falling objects and were admitted to Al Ain Hospital for more than 24 hours, or died after arrival to the hospital were studied for over 3 years. One hundred forty nine patients having a mean age (SD) > 34 (12.1) years were studied. The annual inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
1
5
0
1
Order By: Relevance
“…Spinal and pelvic fractures were possibly caused by high impact injuries. Skeletal limb fractures occur predominantly in same-level falls and injuries from falling objects, findings similar to other studies (11,20,22).…”
Section: Fig 2 External Cause Of Fractures By Age Group and Gendersupporting
confidence: 91%
“…Spinal and pelvic fractures were possibly caused by high impact injuries. Skeletal limb fractures occur predominantly in same-level falls and injuries from falling objects, findings similar to other studies (11,20,22).…”
Section: Fig 2 External Cause Of Fractures By Age Group and Gendersupporting
confidence: 91%
“…They often lack safety equipment and safety education using their own language. We have previously reported the challenges faced with promoting occupational safety in the UAE [ 7 ],[ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nationalities were categorized as Indian subcontinent and others as it had been previously shown that risks of injury for these two groups in Al Ain differed. There is a significantly higher proportion of manual laborers in Al Ain from the Indian subcontinent[ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%